2020
DOI: 10.1111/dth.14584
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of anti‐interleukin 23 biologic drugs in psoriasis patients who failed anti‐interleukin 17 regimens. A real‐life experience

Abstract: Among the most recent biologic drugs available for psoriasis therapy, those targeting interleukin‐17 (secukinumab and ixekizumab) or its receptor (brodalumab) have been shown to be quickly effective. However, in those patients who failed one or more of the above‐cited drugs, real‐life data on the effectiveness of switching to one anti‐interleukin‐23 biologic (guselkumab, risankizumab, or tildrakizumab) are very scarce. Here, we report our experience in treating 12 multi‐failure psoriatic patients, prospectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
53
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(59 citation statements)
references
References 12 publications
6
53
0
Order By: Relevance
“…Moreover, the population was limited to a small-scale and the Western population. 15 18 The patients previously treated with biologics in this study were less likely to achieve PASI 75 than biologic-naïve patients. Furthermore, lower PASI 75 response rate to guselkumab was noted as the number of previous biologics used increased.…”
Section: Discussionmentioning
confidence: 84%
See 4 more Smart Citations
“…Moreover, the population was limited to a small-scale and the Western population. 15 18 The patients previously treated with biologics in this study were less likely to achieve PASI 75 than biologic-naïve patients. Furthermore, lower PASI 75 response rate to guselkumab was noted as the number of previous biologics used increased.…”
Section: Discussionmentioning
confidence: 84%
“…These studies are mostly short-term, have small population sizes, and comprise non-Asian populations. 8 , 15 – 19 , 21 PASI 75 and PASI 90 responses to guselkumab in two short-term (16 weeks) multicentre real-life studies showed that 82.1% and 72.2% of patients achieved PASI 75, whereas 55.4% and 50.6% achieved PASI 90 at week 16. 8 , 15 Our patients responded to guselkumab even worse compared with those in other real-life studies.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations